Nutritional Analysis of Seaweed Chips as An Effort to Reduce Anemia in Adolescent Girls - Manay, Rahma H.; S, Kartini (Indonesian Journal of Global Health Research, 2024)
Adolescence is a critical period that is vulnerable to health issues, including anemia, which is triggered by deficiencies in iron, folic acid, and vitamin C. This study aims to analyze the nutritional content of seaweed chips as an alternative snack to combat anemia in adolescent girls. Using an experimental design, two variants of seaweed chips (original and spicy) were analyzed for their macro- and micronutrient content, including protein, iron, folic acid, and vitamin C. The results showed that the original chips contained an average of 7.1% protein and 39.97 μg/g of iron, while the spicy chips had a higher vitamin C content (67.1%) but lower iron levels (33.1 μg/g). The folic acid content in both variants was very low (<0.25 mg/kg). Nevertheless, the high vitamin C content in the spicy chips can enhance iron absorption, supporting efforts to prevent anemia. Although these seaweed chips cannot be relied upon as a primary source of protein or folic acid, they offer a healthy, low-calorie snack alternative.